Yes means yes! visions of female sexual power & a world without rape - Friedman, Jaclyn 1971-; Valenti, Jessica 1978- (Seal Press, 2019)
Why my mother's subscription to Cosmopolitan was the best and worst thing to happen to my sex life / by Anna Clark -- Sex worth fighting for / by Anastasia Higginbotham -- An immodest proposal / by Heather Corinna -- Why nice guys finish last / by Julia Serano